The Role Of Tuha Peut In Resolving Household Disputes In Gampong Matang Seulimeng, Langsa City - Khairil 'Ulya (International Journal of Sharia Studies, 2024)
The resolution of domestic disputes is not always pursued through formal court channels. In the Matang Seulimeng community, such conflicts are often resolved through the traditional institution known as Tuha Peut. This study aims to examine and analyze the effectiveness of domestic dispute resolution carried out by Tuha Peut using a qualitative method with a sociological empirical approach. Data were collected through interviews with members of Tuha Peut, religious leaders, and individuals who had been involved in previous dispute resolutions. The findings indicate that Tuha Peut plays a significant role in effectively resolving domestic disputes through a process that is fast, simple, cost free, and time efficient. The mediation process emphasizes familial values and deliberation, which not only help de escalate conflicts but also foster justice, peace, and social responsibility among the disputing parties. Therefore, the Tuha Peut institution remains relevant and effective in resolving disputes at the village level.